Asian-Pacific Population Programme News. (ESCAP, 1973)
Chronicles the activities and operations of the Asian and Pacific Population Program for faster awareness and understanding of the size, complexity and significance of the Population problems faced by Governments in the ESCAP region. Reports how ESCAP member countries deal with these problems as an integral part of their economic and social development process.